Biodegradable disulfide crosslinked chitosan/stearic acid nanoparticles for dual drug delivery for colorectal cancer. (15th October 2022) - Sood, Ankur; Gupta, Aastha; Bharadwaj, Ravi; Ranganath, Pavana; Silverman, Neal; Agrawal, Garima
Abstract: Herein, redox responsive chitosan/stearic acid nanoparticles (CSSA NPs) (≈200 nm) are developed for dual drug delivery. These degradable nanoparticles are prepared based on disulfide (SS) crosslinking chemistry avoiding the use of any external crosslinking agent. CSSA NPs are further loaded with both DOX (hydrophilic) and curcumin (hydrophobic) drugs with ≈86 % and ≈82 % encapsulation efficiency respectively. This approach of combining anticancer therapeutics having different mode of anticancer action allows to develop systems for cancer therapy with enhanced efficacy. In vitro drug release experiments clearly exhibit the low leakage of drug under physiological conditions while ≈98 % DOX and ≈96 % curcumin is released after 136 h under GSH reducing conditions. The cytotoxicity experiments against HCT116 cells demonstrate higher cytotoxicity of dual drug loaded CSSA NPs. In vivo biodistribution experiments with c57bl/6j mice confirms the retention of CSSA NPs in the colon area up to 24 h exhibiting their potential for colorectal cancer therapy. Graphical abstract: Unlabelled Image